Tapering for triathlon competition - Mujika, I. (Journal of Human Sport & Exercise, 2011)
The taper is a phase of reduced training before major competitions. Training intensity should be maintained to retain or enhance training-induced adaptations during tapering, but reductions in other training variables should allow for sufficient recovery to optimize performance. Lowering training volume by about 41-60% induces positive physiological, psychological and performances adaptations in highly trained triathletes, but performance benefits could be attained with somewhat smaller or bigger volumes. A final increase of 20-30% of the training load during the last days before a race may be beneficial. High training frequencies (>80%) seem to be necessary to avoid detraining and "loss of feel" in highly trained triathletes. The optimal duration of the taper varies widely, and tapers lasting 4 to 28 days may be ideal for individual athletes. If a temporary increase of about 20% over the normal training load is planned during the month preceding the taper, the duration of the taper should be extended. Particular attention should be given during the taper to recovery strategies, which may help to induce parasympathetic reactivation and muscle fatigue reduction. Adequate hydration, nutrition and carbohydrate loading strategies are recommended to help triathletes perform at their best. Travel, heat and altitude are environmental factors that often need to be integrated within the taper plan, and the need for multiple peaking is another issue that needs to be addressed by coaches and triathletes.